Pengaruh Inflasi Terhdap Daya Beli Masyarakat (Studi kasus: UMKM di Kota Bandung) - Erifebriani (CV. ITTC INDONESIA, 2025)
The sustainability of MSMEs also contributes to the local economy, however these MSMEs often face challenges related to people's purchasing power which is influenced by increasing inflation. The aim of this research is to analyze the effect of inflation on the elasticity of demand and people's purchasing power. The research method uses a descriptive qualitative approach by collecting data through interviews (involving 15 MSME owners in the food and beverage sector in Bandung City, selected by purposive sampling) and observation. Data analysis uses interactive qualitative analysis models with stages of data collection, data reduction, data presentation and drawing conclusions. The research results show that inflation has an impact on reducing consumer purchasing power in the city of Bandung. MSME owners realize that inflation has a big influence on the elasticity of demand and people's purchasing power. However, they face challenges in maintaining stable demand amidst price fluctuations. In the city of Bandung, the impact of inflation and decreasing purchasing power can be seen from changes in people's consumption patterns, who are becoming more selective, choosing more economical products, reducing the frequency of purchases, and switching to online shopping to get more competitive prices.